006 The pharyngeal endoderm in cardiovascular patterning. (22nd September 2015) - Bamforth, S D; Venkatesh, D; Xu, P-X; Kist, R; Peters, H
Abstract : Introduction: Cardiovascular development requires interactions between pharyngeal endoderm, ectoderm, mesoderm-derived and neural crest-derived mesenchyme, and endothelium. Mutations in genes expressed in one or more of these tissues can cause developmental abnormalities of the heart and vessels, as well as other organs of the pharyngeal apparatus. Patients with del22q11 syndrome suffer from cardiovascular, thymus and parathyroid abnormalities and mutations in the transcription factor TBX1 have been implicated as an important genetic defect underlying the del22q11 phenotype. A microarray experiment using Tbx1 null mouse embryos identified a reduction in Pax9 expression. The transcription factor Pax9 is expressed in the pharyngeal pouch endoderm at mid-embryogenesis and mice lacking Pax9 die perinatally with a cleft secondary palate and the thymus, parathyroid glands, and ultimobranchial bodies are absent. However, the role of Pax9 during cardiovascular development has not been investigated. Method and Results: Mice heterozygous for a null allele of Pax9 ( Pax9 lacZ ) were intercrossed and the resulting embryos were processed for analysis by histology, magnetic resonance imaging (MRI), immunohistochemistry and X-Gal staining. In a parallel experiment Pax9 was selectively deleted from neural crest cells by crossing Wnt1Cre transgenic mice with Pax9 flox mice. Pax9 null embryos at E10.5 were examined by PECAM-1 immunohistochemistry, revealing pharyngeal arch artery defects (Abstract 006 Figure 1b ). By E14.5, Pax9 null embryos have major cardiovascular defects including double-outlet right ventricle (DORV), severely hypoplastic aorta, interrupted aortic arch (IAA), and aberrant right subclavian artery (A-RSA), also seen at E15.5 by MRI (Abstract 006 Figure 1d ). We have previously shown that Wnt1Cre -mediated inactivation of Pax9 causes cleft secondary palate and tooth agenesis. In contrast, no abnormalities in the heart, outflow tract or pharyngeal arch arteries were observed. The transcription factor Eya1 is expressed in the pharyngeal endoderm, mesenchyme and ectoderm in the developing mouse, and Eya1 null embryos die perinatally with abnormalities of pharyngeal pouch derivatives. Eya1 is thought to belong to the same genetic network as Pax9 . Embryos null for Eya1 were examined by histology at E15.5 and found to have cardiovascular defects including VSD, DORV, IAA and A-RSA (Abstract 006 Figure 2b ). To investigate whether Pax9 and Eya1 genetically interact, we intercrossed Pax9 +/− ;Eya +/− mice. This revealed that 9/10 compound mutants died at around E10.5 (Abstract 006 Table 1 ). X-Gal staining for Pax9 lacZ in mutant embryos revealed loss of staining and caudal pharyngeal pouch structures (Abstract 006 Figure 2d ). Conclusion: In the mouse, Pax9 expression in the pharyngeal endoderm is vital for correct cardiovascular development. Our data suggest that Pax9 and Eya1, possibly together with Tbx1, genetically interact in the pharyngeal endoderm to control cardiovascular development.